(untitled) (Journal of Insurance Studies in South Asia, 2024)
Agriculture contributes 23.95% of the Nepal’s GDP (MoALD, 2022) employing 57.3% of the total workforce of Nepal (National Census, CBS, 2023). Farmers face a variety of risks, including natural disasters, market-related risks, technical risks, systemic risks such as changing and uncertain legal and regulatory policies, trade and market policies, governance-related uncertainties, weak institutional capacity, and financial risks. Agricultural production is a high-risk activity subject to several contingencies, resulting in volatile and unpredictable farm incomes from year to year. Agriculture insurance provides an opportunity to shift natural risks, increase production and improve the wellbeing and utility of rural households. Agricultural insurance is also widely believed to have played an important role in stabilizing national economic conditions and providing motivation to poor rural households to adopt new technologies. Insurance Board (Beema Samiti), Government of Nepal, has been implementing Agriculture Insurance Program since 2013 but its proper implementation and regulation has not been intensively practiced to date (Bima Samitee, 2019 and Timilsina et al 2018). The descriptive analysis of the data from the 10 years’ period shows that the agriculture insurance sector is growing slowly in Nepal. The performance ratio indicators like loss ratio, break-even ratio, premium to sum insured ratio, claims to sum insured ratio suggests positive environment for insurance companies as well as the farming community i.e. profitability of insurance companies and low burden of premium for farming community.